5S effectiveness at Honda Malaysia Sdn Bhd / Norismaliza Isenin - Isenin, Norismaliza (Faculty of Business and Management, 2006)
The research attemps to analyze the effectiveness of 5S implementation a Honda Malaysia Sdn Bhd. The Issue that the researcher would like to highlight in this study is with regard the quality of effectiveness of 5S in the company. The study identified the level of effectiveness on the 5S implementation and at the same time the study focuses on the quality of this Japanese theory where this theory can provide a safety working environment, cleanliness, save cost, increase sales and create employee and customer satisfaction. This research will be done at Honda Malaysia Sdn Bhd, Alor Gajah Malacca. A total number of 297 employees has been randomly selected from 1237 employees as the sample. They will be given a set of questionnaire to be answer related to 5S effectiveness and the factors to the effectiveness. From the outcome of the questionnaire later, the data will be analyze and interpret using the Statistical Package for the Social Science (SPSS) software to identify the relationship that believe to exist among the dependent variable (5S effectiveness) and all the independent variables (top management involvement, promotional campaign, keeping records, 5S Training, Evaluation and Maintaining the System) Research objectives answered of this study are to determine factors that influence 5S effectiveness at Honda Malaysia Sdn Bhd, to Identify relationship between the factors and 5S effectiveness and lastly to give solutions or recommendations to increase 5S effectiveness.